Adaptive beam-shaping enabled high-precision patterned laser micro-grooving - Pei Qiu; Jun Li; Dandan Yuan; Zixuan Xin; Jiaxu Huang; Shaolin Xu (International Journal of Extreme Manufacturing, 2025)
Microgrooves with diverse cross-sections are required in various fields but remain a significant challenge in precision machining, especially for hard-to-machine materials. Patterned laser ablation offers an avenue for fabricating microgrooves on any material with notably enhanced shape diversity. However, it is hard to precisely control the grooves’ cross-sectional profiles due to the complex ablation process, including the diffraction-induced energy distribution variations away from the focal plane and the inconsistent polarization-related energy absorption. These factors complicate the relationship between beam spot shape and ablated groove shape, making it challenging to design appropriate spot shapes for specific groove requirements. Here, we propose an adaptive beam-shaping method for laser spot design to improve microgrooves’ shape accuracy. Combining laser diffraction and polarization effects, a profile evolution model of the laser ablation is established to accurately predict groove shapes, guiding the iterative beam-shaping procedure. The beam spot shape is iteratively fine-tuned until the deviation between the simulated and the target grooves’ profile meets the accuracy requirements. The grooves’ profile deviations are significantly reduced, with the final profile’s root mean square error decreased to less than 0.5 μm when processing microgrooves with a width of 10 μm. Various microgrooves with precise cross-sections, including triangles, trapezoids, and functionally contoured microstructures, are achieved by patterned laser direct writing assisted with the adaptive beam-shaping method. This method paves the way for laser ablation of microgrooves with high shape accuracy for traditional hard-to-machine materials.